Vicious. The complete second season [videorecording (DVD)] - Jacobi, Derek; McKellen, Ian; De la Tour, Frances, 1944- (PBS Distribution, 2015)
Tells the comedic story of aging partners Freddie and Stuart, two men who have lived together in their Covent Garden flat for nearly 50 years.